Ecological status assessment of lakes using macrophytes - Chilińska, Elżbieta (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2015)
Harmonisation of the laws of the Member States regarding the protection of the environment is one of the tasks of the European Union. Poland joined EU in 2004 and took on various commitments for the improvement of water status. In particular, the Water Framework Directive was a major breakthrough in the assessment of aquatic ecosystems. For the classification of stratified and non-stratified lakes Ecological State Macrophyte Index (ESMI) has been used. In Poland, the method for assessing the ecological status of lakes based on macrophytes has been developed for routine water monitoring shortly after joining the European Union. This index is one of the biological elements in the assessment of ecological status. It considers the whole plant communities in the reservoir. The key factor that ESMI reacts to is anthropopressure, which manifests itself as eutrophication. However, it is crucial that the lakes are also subject to different pressures. In this situation, the ESMI rating becomes only an indicative method. The article describes the role, process of evaluation and the most common problems related to ESMI.